The Importance of Attestation Prior to the Registration of Instruments under the National Land Code 1965 - Natasha Halid, Shahrul; Zaidi Hass, Jady (International Journal of Engineering and Technology, 2018)
Recent events had put the question of security of land transactions at the forefront of not only the political and economic agenda worldwide, but also posed some key questions for law and the future regulation of property rights. The Torrens System of land registration which is practiced in Malaysia can be traced back to Sir Robert Torrens in South Australia during the late eighteenth century. The land registration system should be made flexible enough to adapt to the changing of technologies but also secure enough to ensure that the registered proprietors have good title to their lands. This article is intended to explore the rigorous and somewhat tedious process that is provided under the National Land Code 1965 relating to the attestation of instruments before the presentation for registration.Â Â